Using Focus Groups to Validate a Pharmacy Vaccination Training Program - Mary Bushell; Hana Morrissey; Patrick Ball (MDPI AG, 2015)
Introduction: Focus group methodology is commonly used to quickly collate, integrated views from a variety of different stakeholders. This paper provides an example of how focus groups can be employed to collate expert opinion informing amendments on a newly developed training program for integration into undergraduate pharmacy curricula. Materials and methods: Four focus groups were conducted, across three continents, to determine the appropriateness and reliability of a developed vaccination training program with nested injection skills training. All focus groups were comprised of legitimate experts in the field of vaccination, medicine and/or pharmacy. Results: Themes that emerged across focus groups informed amendments giving rise to a validated version of a training program. Discussion: The rigorous validation of the vaccination training program offers generalizable lessons to inform the design and validation of future training programs intended for the health sector and or pharmacy curricula. Using the knowledge and experience of focus group participants fostered collaborative problem solving and validation of material and concept development. The group dynamics of a focus group allowed synthesis of feedback in an inter-professional manner. Conclusions: This paper provides a demonstration of how focus groups can be structured and used by health researchers to validate a newly developed training program.